MODAL SOSIAL DALAM USAHA PENGEMASAN GARAM BERYODIUM USAHA DAGANG INDRA AGUNG DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Wanda Saputra; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
research is based on the development of UD. Indra Agung owned by Umar Lubis in Mandau sub-districts , Bengkalis districts developed quite rapidly. In its development UD. Indra Agung is not subject to the factors of social capital in it. This study uses social capital theory to analyze the phenomenon that occurs. The purpose of this study is to determine the elements of social capital in the development of UD. Indra Agung, and constraints faced by business owners in its development. Qualitative methodology as a research procedure that produces descriptive data in the form of written or oral words of people and behavior that can be observed. Data collection techniques that researchers will use is to use an interview method which is a form of verbal communication or conversation with the intention of obtaining information from the object, and the method of observation. Data analysis using qualitative descriptive. The results of this study, the authors found that there are elements of trust in which there is an element of honesty and tolerance, network elements, and also elements of religious norms. Also in the process of development of UD. Indra Agung has constraints on either external constraints or internal constraints.Keywords: social capital, Usaha Mikro Kecil Menengan (UMKM), Mandau sub-districts, Bengkali Districs.